Relationship between general CSR management practices and the development of internal social responsibility (Journal of Business, Universidad del Pacífico (Lima, Peru), 2021)
Companies that embrace corporate social responsibility (CSR) tend to adopt certain general practices, such as: establishing social responsibility areas, preparing codes of ethics, publishing social or sustainability reports, joining organizations that promote social responsibility, or starting their own foundations. The question then arises as to whether these general practices actually influence the responsible behavior of companies. This article explores the relationship between the application of these general CSR practices and the level of development of internal social responsibility (ISR). To study this relationship, information was drawn from the system of CSR indicators (CSRI) overseen by the Cristian Association of Business Managers (Asociación Cristiana de Dirigentes de Empresas, a self-evaluation system in which Uruguayan companies participate annually. The CSRI uses 25 indicators to measure the level of ISR development and record the application of eight general CSR practices. After carrying out a review of the literature, the 25 indicators were organized into nine dimensions of ISR: employees’ human rights; informing employees about issues that affect them; occupational health and safety; internal environment; personal and professional development; employment protection; voluntary provision of benefits; union relations; and fair pay. After analyzing the statistical correlation between the application of general CSR practices and the level of development of social responsibility across the nine dimensions, the results indicate the following: three general practices positively correlate with the development of ISR in all its dimensions (including CSR in strategic planning, involving the management team in CSR issues, and joining an organization that promotes CSR); one practice (preparing a code of ethics) correlates with half of the dimensions; and the other four practices (publishing a social or sustainability report, assigning a full-time employee to CSR management, having a CSR team or area, and possessing a foundation) correlate with none or almost none of the dimensions.